A tessitura da memória em o vendedor de passados de José Eduardo Agualusa - Bezerra, Ana Cristina Pinto (2013)
In the study of African literature in Portuguese language, the theme importance of memory is done by contact those literary works have with the context in which they operate. This study aims to reflect how memory as social element becomes an agent of the composition of literary structure in the O Vendedor de Passados (2004), by José Eduardo Agualusa. Therefore, we have as reference the critical method developed by Antonio Candido (1976), regarding the critical dialectic, in order to understand how such a throwback acts in the structuring of the romance in a relationship with both structural and thematic elements. Firstly, it presents a panoramic reading the Angolan literary scene in the post-independence, relating this context with the route of writing of José Eduardo Agualusa. Then it performs the analysis of the relationships between narratives categories - narrator, characters, space, time - and the memorial element, keeping in mind that these categories would be constructed in dialogue with the memory. Lastly, there is the reflection on the dynamics between fiction and reality apprehended in novelistic discourse in which a seller of past figures in an analysis that takes place from the skeptical look on this work. As a theoretical approach, we highlight mainly readings: Hampaté-Bâ (2010), Laura Padilla (2007), Tania Macêdo (2008) for the observation of the specific African context quickened in the novel; Tedesco (2004), Halbwachs (2006), Le Goff (2003) regarding the conceptualisation of memory; and Landesman (2006), Krause (2004), Gai (1997) in cutting the skeptical outlook with which the romance dialogues